Self-decoupled quad-port CPW-fed fractal MIMO antenna with UWB characteristics - Binghao, Wang; Kamarudin, Muhammad Ramlee; Muhammad Kamal, Mian; Shoaib, Nosherwan; Rafque, Umair; Abbasi, Muhammad Inam (Hindawi Limited, 2024)
In this work, a novel fractal multiple-input multiple-output (MIMO) antenna is designed for ultrawideband (UWB) applications. The radiating structure of the MIMO confguration employs a circular fractalradiating structure excited through a modifed coplanar wave guide (CPW) feed. Te fractal shape is designed by employing small circular rings inside the main circular ring patch element, whichled to enhanced impedance bandwidth spanning from 3.15 to 20 GHz with acceptable radiation properties. Te results show that the designed antenna has a peak gain of 6.13 dBi and radiation efciency of > 85% in the operating bandwidth. Moreover, the single-antenna element exhibits stable radiation patterns in the UWB frequency spectrum. For MIMO communication systems, a polarization diversity-based quad-port MIMO antenna is designed. From the designed MIMO antenna confguration, an isolation of > 15 dB is achieved among the radiating elements without the use of any isolation enhancement network. Furthermore, MIMO performance parameters such as envelope correlation coefcient (ECC) of < 0.008, mean efective gain (MEG) of < − 3 dB, channel capacity loss (CCL) of < 0.25 bps/Hz,and total active refection coefcient (TARC) of > 20 dB are obtained from the proposed UWB MIMO antenna.